Autonomic function test in progressive lacunar infarction - Ha, S. Y.; Park, K. M.; Park, J.; Kim, S. E.; Lee, B. I.; Shin, K. J. (Acta neurologica Scandinavica, 2018)
Objective Neurological progression is a major problem in managing the patients with acute lacunar infarction. The purpose of this was to investigate whether autonomic dysfunction is associated with neurological progression in patients with acute lacunar infarction. Materials and Methods The study comprised 60 patients with acute lacunar infarction. All enrolled subjects underwent autonomic function tests including the 30° head‐up tilt test, Valsalva test, heart rate response to deep breathing, and sympathetic skin response. The primary endpoint is the neurological progression, and the secondary endpoint is the 3‐month outcome. Results Increased initial National Institute of Health stroke scale (NIHSS), decreased time to admission from onset, decreased rise of heart rate in the 30° head‐up tilt test, abnormal blood pressure response in the Valsalva test, and decreased rise of systolic blood pressure in stage IV of the Valsalva test are associated with neurological progression of acute lacunar infarction; an abnormal blood pressure response in the Valsalva test is significant in logistic regression analysis of neurological progression. Advanced age, increased initial NIHSS and modified Rankin scale, decreased expiration/inspiration ratio of heart rate to deep breathing, decreased rise of systolic blood pressure in stage IV of the Valsalva test, and neurological progression were associated with an unfavorable 3‐month outcome; neurological progression was significant in logistic regression analysis of 3‐month outcome. Conclusions An abnormal blood pressure change in the Valsalva test is associated with neurological progression in patients with acute lacunar infarction, and neurological progression can induce an unfavorable 3‐month outcome.